Eficiencia del pasto vetiver (Chrysopogon zizanioides) ex – situ en la remoción de contaminantes orgánicos, caso de estudio río muerto, cantón Manta - Santana Suárez, Ximena Valeria (2016)
The objective of this research was to evaluate the efficiency of vetiver grass (Chrysopogon zizanioides) ex - situ in the removal of organic pollutants in the waters of the Muerto river in the town of Manta, for which a design was completely randomized with four treatments using 30, 12 and 2 cuttings of vetiver grass under hydroponic conditions and a witness. The grass was put in a volume of 20 liters of water from the river each with three repetitions, monitoring them every eight days where they dissolved oxygen, pH and salinity then also removed nitrogen, phosphorus, turbidity and BOD, the experiment lasted four weeks. As the results, was verified with the diagnosis of the samples, the Muerto river has a high concentration of organic and inorganic matter COD (1975 mg/L), causing a low level of dissolved oxygen of 0.51 mg/L. Vetiver grass cuttings used in the experiment were removed of contaminants and dissolved oxygen increased in all experimental units from the first week reflecting its adaptability and development each passing day; both treatment A2 (2 cuttings + 20 L), and A3 (12 cuttings + 20 L) showed statistically significant differences versus control for BOD removal at 15 days, with a significance of P= 0.016 and P= 0.037, respectively. Also, for turbidity significant differences within the 8 days were found: A3 (P= 0.014) A2 (P= 0.004). However, the third treatment, A3 proved very efficient in the end: BOD (72.92%), nitrogen (84.09%), phosphorus (65.04%) and turbidity (76.76%), and an increased level of DO to 5.04 mg / L was observed.